2015
DOI: 10.1002/ece3.1553
|View full text |Cite
|
Sign up to set email alerts
|

Reconciling actual and perceived rates of predation by domestic cats

Abstract: The predation of wildlife by domestic cats (Felis catus) is a complex problem: Cats are popular companion animals in modern society but are also acknowledged predators of birds, herpetofauna, invertebrates, and small mammals. A comprehensive understanding of this conservation issue demands an understanding of both the ecological consequence of owning a domestic cat and the attitudes of cat owners. Here, we determine whether cat owners are aware of the predatory behavior of their cats, using data collected from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
31
0
5

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(39 citation statements)
references
References 35 publications
3
31
0
5
Order By: Relevance
“…Consequently, many conservation initiatives have been aimed at the eradication of feral cats on islands (Nogales et al 2004), but the threat that free-ranging house cats pose to wildlife is also serious and has gained recognition by both researchers and conservationists (e.g., Kays and DeWan 2004;Baker et al 2005;Sims et al 2008;Morgan et al 2009;Bonnington et al 2013). While there is a set of mitigation measures that can be considered (reviewed in Calver et al 2011), the application of any of them requires cooperation with cat owners, who often fail to understand the detrimental effect their pets can have on wildlife (McDonald et al 2015). Thus, studies showing the diversity of animal species that are killed by cats as well the magnitude of their hunting pressure are important; they both inform public opinion about the problem and can help raise financial support for mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, many conservation initiatives have been aimed at the eradication of feral cats on islands (Nogales et al 2004), but the threat that free-ranging house cats pose to wildlife is also serious and has gained recognition by both researchers and conservationists (e.g., Kays and DeWan 2004;Baker et al 2005;Sims et al 2008;Morgan et al 2009;Bonnington et al 2013). While there is a set of mitigation measures that can be considered (reviewed in Calver et al 2011), the application of any of them requires cooperation with cat owners, who often fail to understand the detrimental effect their pets can have on wildlife (McDonald et al 2015). Thus, studies showing the diversity of animal species that are killed by cats as well the magnitude of their hunting pressure are important; they both inform public opinion about the problem and can help raise financial support for mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…However, if owners do not see their pet's behaviour as unusual or problematic, they may be less likely to voluntarily assume responsibility for managing it. This phenomenon is heightened by the broader societal acceptance, in the United Kingdom, of unconstrained roaming by owned cats (McDonald et al, ; Thomas et al, ), even when compared to culturally similar countries such as the USA and Australia (Hall et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As in Thomas et al's () study, a substantial proportion (60%) did not consider cats to be harmful to wildlife. McDonald et al's () study did not find owner opinions to be influenced by their cats’ predatory behaviour.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In the UK, cat owners are often unwilling to admit that their pets may be a threat to wildlife (McDonald et al 2015). Recent research has suggested that advocacy campaigns for cat containment that focus on the benefits to cat welfare, rather than wildlife conservation, may be more successful (MacDonald et al 2015;Hall et al 2016) and that a better understanding by cat owners of the risks encountered by free-ranging cats may result in behaviour change (Gramza et al 2016).…”
Section: Social Studiesmentioning
confidence: 99%